2022
DOI: 10.3390/foods11172568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fruit Storage Temperature and Time on Cloud Stability of Not from Concentrated Apple Juice

Abstract: Apple juice that is designated ‘Not from concentrated’ (NFC) is now increasingly popular with consumers due to its unique taste and rich nutritional value. However, layered precipitation and instability have emerged as serious technical problems that restrict the viability of the NFC apple juice industry. This study researched the influence of water-cored ‘Fuji’ apple fruit storage under different temperatures (0, 20 °C) and times (0, 9, 18, 30, 60 days) on the turbidity stability of NFC apple juice. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
2
2
0
Order By: Relevance
“…The addition of the biosurfactant extract to the pasteurized apple juice affected the pH values, causing a slight reduction when increasing the concentration of the biosurfactant extract, but the changes were minimal and the pH values ranged from 3.35 to 3.48, suggesting that the biosurfactant extract maintained the chemical properties and stability of apple juice regarding pH variations. These pH values are in good agreement with those previously reported in apple juice, which were increased from 3.91 to 4.13 when the storage time was extended from 0 to 90 days [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The addition of the biosurfactant extract to the pasteurized apple juice affected the pH values, causing a slight reduction when increasing the concentration of the biosurfactant extract, but the changes were minimal and the pH values ranged from 3.35 to 3.48, suggesting that the biosurfactant extract maintained the chemical properties and stability of apple juice regarding pH variations. These pH values are in good agreement with those previously reported in apple juice, which were increased from 3.91 to 4.13 when the storage time was extended from 0 to 90 days [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 92%
“…Other authors [ 22 ] also confirmed the significant increase of total sugars in different pasteurized fruit juices, including apple juice, after thirty days of storage time at refrigeration temperature but evaluating the sugar progressions after ten day intervals. Moreover, Wang et al [ 23 ] evaluated the effects of storage temperature and time on the stability of concentrated apple juice. These authors observed that the increase in temperature (0 to 20 °C) and storage time (0, 15, 30, 60 to 90 days) caused a decrease in the total sugar content from 117 to 112 g/L or from 117 to 110 g/L when the storage time was extended up to 90 days or the incubation temperature increased from 0 to 20 °C, respectively, probably due to the rate of soluble sugar consumption by the microbial biomass being higher than the rate of hydrolysis of polymeric sugars.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the obtained findings agree with DERELI et al (2015), DAVARCI et al (2019), WANG et al (2022) and ALUKO et al (2023.…”
Section: Resultssupporting
confidence: 86%
“…Additionally, pH also has a great influence on phenolic compounds, and it has been found that the sensitivity of phenolic compounds to pH is closely related to the structure of phenol, for example, epigallocatechin (EGC; a gallic acid ester) is stable at high pH, while gallic acid is unstable, and 1,2,3,4,6‐penta‐ O ‐galloyl‐β‐ d ‐glucose is prone to hydrolysis under acidic conditions (Friedman et al., 2000; Huang et al., 2019). In recent years, although more and more researchers have been interested in this field, most of them have focused on lychee juice, orange juice, apple juice, few studies concentrated on P. emblica juice, especially the effect of storage temperature and pH on its phenolic compounds (Capito et al., 2021; Pokhrel et al., 2022; Wang et al., 2019, 2022). Therefore, it is very necessary to research the effect of storage temperature and pH on phenolic compounds in P. emblica juice, which provides a certain reference and scientific basis for the storage conditions of P. emblica juice.…”
Section: Introductionmentioning
confidence: 99%